Peningkatan keterampilan menulis deskripsi melalui model concept sentence kelas II sekolah dasar - Ria Dwi Wulandari; Retno Winarni; Chumdari Chumdari (Universitas Sebelas Maret, 2019)
Abstract. This study aimed to increase the descriptive writing skill by using the Concept Sentence model of the second-grade students at Public Elementary School Karangasem II Surakarta in the academic year 2018/2019. The subjects of this study are one teacher and 29-second grade students at Public Elementary School II Surakarta. The type of this research is classroom action research. This research consists of two cycles and every cycle consists of four stages. They are; planning, action, observation, and reflection. In collecting data, the researcher uses: observation, interview, test, and documentation. The data validity test techniques used are; source triangulation, technical triangulation, and content validity. The data analysis technique used in this study is interactive analysis model including data reduction, data display and drawing a conclusion. The finding of this study shows that the application of Concept Sentence model can improve descriptive writing skills students. It can be compared to the score result in the pretest and each cycle. In pretest, the classical completeness score of the descriptive writing skill is 13,79% and then up to 76,42 in the cycle 1, and the score gained in cycle II is 86,21%. It can be concluded that the use of Sentence model can improve the descriptive writing skills of the second grade students at Public elementary School Karangasem II Surakarta in the academic year 2018/2019.Keyword: descriptive writing skills, Concept Sentence model